KIDNEY TRANSPLANTATION FROM DONORS AFTER CARDIAC DEATH - R.L. Rozental; Y.L. Ushinskis; S.V. Trushkov; Y.B. Bitsans; V.N. Shevelev; A.V. Malcev (Вестник трансплантологии и искусственных органов, 2012)
From 668 kidney transplantations performed during the period 2000–2005 68 grafts were recovered from donors after cardiac death and 176 from donors with confirmed brain death. Early results (number of primarily non-functioning grafts, rates of delayed graft function and acute rejections) were similar in both groups. 5-year patient survival was 85% from donors after cardiac death and 88% from donors with confirmed brain death. 5-year graft survival was 77% and 85%, respectively. Results showed that the use of kidney grafts recovered from donors after cardiac death is valuable additional source of donor organs.